Influences of Pistacia terebinthus L. and Rhus coriaria L. fruits extracts on the levels of some biochemical parameters in liver tissue of Experimental Breast Cancer rats - Ozsahin, Ayse Dilek; Erdem Erisir, Figen; Tuzcu, Zeynep (Progress in Nutrition, 2021)
In this study, against to DMBA-induced breast cancer healing effects of Pistacia terebinthus L. subsp. Palaestina (terebinth) and Rhus coriaria L. (sumac) were examined as biochemical in the female Sprague-Dawley rats. 66 rats were used in this study. Rats were divided into 6 groups as Control, DMBA, PT, RC, PT+DMBA and RC+DMBA. DMBA was administered by gavaged, a single dose of 80 mg/kg according to body weight, to 8-week-old rats. Aqueous extracts of terebinth and sumac were given orally 3 days a week to rats in antioxidant groups. Malondialdehyde, glutathione, vitamin, cholesterol, antioxidant enzyme and fatty acid levels, which are signs of lipid peroxidation, were measured in liver tissue. At the end of the study in cancerous rats, malondialdehyde increased compared to the control group. Glutathione decreased in the other tissues and all of the DMBA-induced cancerous rats groups. Lipophilic vitamins and cholesterol levels were analyzed by HPLC. The levels were different in DMBA and antioxidant groups of tissues. In cancerous rats, liver cholesterol levels decreased. The results of the present study showed that the herb suspensions exerted anti-cancer effects and consequently may alleviative liver damage caused by DMBA-induced breast cancer.